Carbon Fibers Embedded With Iron Selenide (Fe3Se4) as Anode for High-Performance Sodium and Potassium Ion Batteries - Mahmood, Asif; Ali, Zeeshan; Tabassum, Hassina; Akram, Aftab; Aftab, Waseem; Ali, Rashad; Khan, Muhammad Waqas; Loomba, Suraj; Alluqmani, Ahmed; Adil Riaz, Muhammad; Yousaf, Muhammad; Mahmood, Nasir (Frontiers in Chemistry, 2020)
The development of sodium and potassium ion batteries (SIBs/KIBs) has seen tremendous growth in recent years due to their promising properties as a potential replacement for lithium-ion batteries (LIBs). Here, we report ultrafine iron selenide (Fe3Se4) nanoparticles embedded into one-dimensional (1D) carbon fibers (Fe3Se4@CFs) as a potential candidate for SIBs/KIBs. The Fe-based metal-organic framework particles (MOFP) are used as a Fe source to obtain highly dispersed Fe3Se4 nanoparticles in the product. The Fe3Se4@CF consisted of ultrafine particles of Fe3Se4 with an average particle size of ~10 nm loaded into CFs with an average diameter of 300 nm. The product exhibited excellent specific activity of ~439 and ~435 mAh/g at the current density of 50 mA/g for SIBs and KIBs, respectively. In addition, the as-prepared anodes (Fe3Se4@CFs) exhibited excellent capacity retention up to several hundred cycles (700 cycles for SIBs and 300 cycles for KIBs). The high activity and excellent stability of the developed electrodes make Fe3Se4@CFs a promising electrode for next-generation batteries.